2009
DOI: 10.3748/wjg.15.4273
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis and systematic review of colorectal endoscopic mucosal resection

Abstract: AIM:To evaluate the proportion of successful complete cure en-bloc resections of large colorectal polyps achieved by endoscopic mucosal resection (EMR). METHODS:Studies using the EMR technique to resect large colorectal polyps were selected. Successful complete cure en-bloc resection was defined as one piece margin-free polyp resection. Articles were searched for in Medline, Pubmed, and the Cochrane Control Trial Registry, among other sources. RESULTS:An initial search identified 2620 reference articles, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 32 publications
1
49
0
1
Order By: Relevance
“…Therefore, all colonic lesions C6 mm should be either resected or ablated [4]. From the results of meta-analyses, polypectomy [4] and EMR [6]/ ESD [7] can be considered the preferred less invasive treatments for colorectal neoplasia [8,9]. However, for flat and depressed lesions, endoscopic resection is recommended, since the incidence of carcinoma is even higher in lesions that are B5 mm in size than in polypoid lesions [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, all colonic lesions C6 mm should be either resected or ablated [4]. From the results of meta-analyses, polypectomy [4] and EMR [6]/ ESD [7] can be considered the preferred less invasive treatments for colorectal neoplasia [8,9]. However, for flat and depressed lesions, endoscopic resection is recommended, since the incidence of carcinoma is even higher in lesions that are B5 mm in size than in polypoid lesions [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Advances in technology, such as magnification lenses, narrow band imaging and chromoendoscopy have increased the detection yield for early cancers during colonoscopy [15][16][17] . Lesions characterized as early cancers can be endoscopically resected at the same sitting and can be curative [18,19] . However, the advantages of colonoscopy are not only limited to the detection and treatment of early cancers.…”
Section: Introductionmentioning
confidence: 99%
“…During a mean follow up of 40 months, benign recurrences were observed in only 3% of patients [Doniec et al 2003]. A recent meta-analysis which included 25 studies, however, showed lower pooled rates of complete curative en bloc resections at 59% [Puli et al 2009]. Our experience (unpublished data) suggests that the incidence of polyp recurrence after en bloc resection is 60% less compared with piecemeal resection and additional use of APC did not improve the recurrence rates.…”
Section: Squamous Dysplasia and Cancermentioning
confidence: 65%